Research into corrosion and electrocatalytic properties of the modified oxide films on tin - Plyasovskaya, Kateryna; Vargalyuk, Victor; Sknar, Irina; Cheremysinova, Anna; Sigunov, Oleksii; Karakurkchi, Ann (Eastern-European Journal of Enterprise Technologies, 2017)
Oxide films on tin, modified by titanium compounds, are nontoxic and serve as anticorrosion protection, material for gas sensors, photo and electrocatalysts. We investigated the process of anodic tin treatment in the presence of potassium metatitanate. It is shown that the twostage technique for the formation of an oxide film at the electrode potentials of −0.3 V and 3.0 V makes it possible to substantially increase the content of titanium oxide compounds in the oxide mixture. The content of Ti(IV) reaches values of 14−15 % (mol). Films with a maximum content of titanium compounds and the largest corrosion resistance are formed at a concentration of potassium metatitanate above 1·10–3 mol/l. The time of selfactivation of such films is 10 times longer than that of the unmodified films. We explored catalytic properties of the obtained films with mixed composition SnОх(TiОу). It is shown that an increase in the content of titanium oxide compounds in the film contributes to the acceleration of anodic oxidation of MTBE. It was established that this process takes place directly on the surface of the oxide film rather than during interaction with oxygen formed on the anode. The modified oxide films SnОх(TiОу) on tin with maximal corrosion resistance and electrocatalytic activity are formed from the solutions that contain 0.5M KOH.